WAJIB PAJAK: ASAS, MANFAAT DAN LEGALITASNYA DALAM HUKUM ISLAM - Wahyu Abdul Jafar (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
This study comprehensively describes taxpayer law's legality in Islam, its principles and its benefits. This research is a literature study with a normative juridical approach. The data collection technique used in this research is the documentation technique. At the same time, the analysis technique used in this research is descriptive. The primary data in this study are online scientific journals and books directly related to the object being researched, namely online scientific journals or books related to taxpayers: principles, benefits and legality in Islamic law. From this research, it can be concluded that tax legality in Islamic law is permissible. The legal basis of this tax law is based on the Qur'an, al-Hadith and the opinions of the scholars. Taxes are allowed but with due regard to certain conditions; namely, they must be fair, equitable and not burden the people. In comparison, the principles of tax collection include the principle of territory, the principle of nationality, the principle of sources, and the principle of equality. Tax benefits include helping economic growth, providing sources of revenue for state financing, providing employment, distribution of wealth and income and increasing savings by limiting the consumption of unnecessary goods that have no use and are only ceremonial.